Passing the Threshold of One Justice System to the Next: Challenges of Emerging Young Adults in Hong Kong’s Adult Criminal Justice Process - Cheng, Kevin Kwok-yin (International journal of offender therapy and comparative criminology, 2018)
In many criminal justice systems, there is a clear separation for juvenile and adult defendants. However, those in between, referred to as emerging young adult defendants (ages 18-25 years), are treated as adult defendants despite a growing recognition that emerging adulthood is a distinct period in the life course. The aim of this present study is to investigate the experiences and challenges faced by emerging young adult defendants (N = 25) in Hong Kong’s adult criminal justice process. Through in-depth semistructured interviews, it was found that emerging young adult defendants demonstrated a lack of understanding regarding their rights and the legal procedures, faced stress in being caught up in the criminal justice process, and were susceptible to influence by others, particularly family members, in making legal decisions. Implications and future directions of study are discussed.